Model Bimbingan Kelompok dengan Menggunakan Metode Role Playing dalam Mengurangi Kecemasan Berkomunikasi - Dina Anggrawati; Fitria Kasih; Rici Kardo (JAMBURA Guidance and Counseling Journal, 2021)
This research is motivated by the students' communication anxiety that has not been achieved and there are Counseling Guidance Teachers who have not used varied methods in implementing group guidance. The purpose of the study was to describe: a). The profile of students' communication anxiety levels, b). The implementation of group guidance by BK teachers using the role playing method. c). The design model of group guidance services using the role playing method in helping reduce the level of communication anxiety of students. This research was conducted using a mixed method. The sampling technique used was total sampling with 30 participants. While qualitative research, the key informants of the research are 1 BK teacher class XI MIPA 1 and 2 additional informants. The instruments used are questionnaires and interviews. The data analysis technique used statistical test tools. The technique used in data processing is the percentage. For qualitative data analysis through data reduction, data presentation and drawing conclusions. Keywords: Communication Anxiety, Students